Constructing the International Business Image of Guangzhou: A Corpus-driven Discourse Analysis of Business News on Government Website - Yan, Fangyuan (International Journal of Linguistics, Literature and Translation, 2026)
In the context of globalization, cities serve as pivotal actors in international competition, where their international image and business environment play decisive roles in attracting investments, talents, and fostering economic growth. Guangzhou, as southern China’s economic nucleus, strategically constructs its international business persona and disseminates business environment information through official platforms like government portals. This study conducts a comprehensive discourse analysis of business news on Guangzhou’s government website, aiming to reveal linguistic characteristics, rhetorical strategies, and their impact on the city’s commercial identity. Employing a corpus-driven discourse analysis framework, this research collected and analyzed English business news published on Guangzhou Municipal Government’s official portal (gz.gov.cn) from August 2023 to June 2024. The theoretical framework includes LDA topic modeling, Sinclair’s extended meaning unit theory, and Wodak’s discourse strategies, exploring the construction mechanism and optimization pathways of Guangzhou’s international business image. The research identifies four core business images: a global trade hub, an innovation-led tech hub, a highly attractive investment destination, and a dynamic and livable metropolis. It reveals the synergistic application of four key discursive strategies: nomination, predication, argumentation, and intensification/mitigation. Furthermore, specific enhancement pathways are proposed from three dimensions: linguistic optimization, government website upgrading, and cross-dimensional collaboration. This study provides a theoretical framework and practical reference for the international communication of urban business images.